A STUDY ON THE IMPACT OF ENVIRONMENTAL EDUCATION AT PRIMARY LEVEL STUDENTS AND ENVIRONMENTAL AWARENESS PROGRAMMES CONDUCTED BY TEACHER IN PRIMARY SCHOOLWITH SPECIAL REFERENCE TO SIVASAGAR DISTRICT, ASSAM - GitashreeGogoi, NitumoniSaikia (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Environmental education is a major part of the curriculum that helps in developing a deeper understanding of environmental issues. The main objectives of the study was to learning abilities, knowledge and skills of students from environmental education and to study the awareness programmes conducted by teachers to create the awareness among the primary level students. Descriptive research method was used for the study. The sample consisted of the study 50 teachers and 100 students of Sivsagar District and purposive sampling technique used. For the study the researcher used a self constructed questionnaire schedule. Findings of the study revealed that environmental education play the significant role at primary level students to create awareness towards the environment and also it was found that primary school teachers organized various activities both inside and outside the class to understand the environmental problems as well as strategies to solve the problems.